Discovery of a planetary-mass companion within the gap of the transition disk around PDS 70 - Keppler, Miriam; Henning, Thomas; Brems, Stefan S. (Astronomy and astrophysics, 2018)
Young circumstellar disks are the birthplaces of planets. Their study is of prime interest to understand the physical and chemical conditions under which planet formation takes place. Only very few detections of planet candidates within these disks exist, and most of them are currently suspected to be disk features. In this context, the transition disk around the young star PDS 70 is of particular interest, due to its large gap identified in previous observations, indicative of ongoing planet formation. We aim to search for the presence of an embedded young planet and search for disk structures that may be the result of disk-planet interactions and other evolutionary processes.
Gesehen am 30.01.2019